Multiplexing 32,000 spectra onto 8 detectors: the HARMONI field splitting, image slicing and wavelength selecting optics - Tecza, M; Thatte, N; Clarke, F; Freeman, D; Komalski, J (2012)
HARMONI, the High Angular Resolution Monolithic Optical and Near-infrared Integral field spectrograph is one of two first-light instruments for the European Extremely Large Telescope. Over a 256x128 pixel field-of-view HARMONI will simultaneously measure approximately 32,000 spectra. Each spectrum is about 4000 spectral pixels long, and covers a selectable part of the 0.47-2.45 μm wavelength range at resolving powers of either R=4000, 10000, or 20000. All 32,000 spectra are imaged onto eight HAWAII4RG detectors using a multiplexing scheme that divides the input field into four sub-fields, each imaged onto one image slicer that in turn re-arranges a single sub-field into two long exit slits feeding one spectrograph each. In total we require eight spectrographs, each with one HAWAII4RG detector. A system of articulated and exchangeable fold-mirrors and VPH gratings allows one to select different spectral resolving powers and wavelength ranges of interest while keeping a fixed geometry between the spectrograph collimator and camera avoiding the need for an articulated grating and camera. In this paper we describe both the field splitting and image slicing optics as well as the optics that will be used to select both spectral resolving power and wavelength range. © 2012 SPIE.